Genetic and environmental factors on age at first calving of Gir cows. - Ramos, Alcides de Amorim; Polastre, Rinaldo; Filho, Jaime Laperuta (Pesquisa Agropecuaria Brasileira, 2014)
The purpose of this study was to evaluate the genetic and environmental effects on age at tirst calving of 986 Gir cows that were born from 1959 to 1975, in six herds. Data were analysed by the least square method using the effects of herd, sire within herd, season and year of birth of heifers. The average age of cows was 1,430 ± 266 days or 46.94 months (CV = 18,59%). The analysis of variance showed significant effects (P< .01) for herds, sire within herd and birth year, explaining, 11.53: 9.19 and 7.44% of addition of total square (R2), respectivelly. The difference between herds have reached 413 days or 13.54 months (P< .01) when Tukey's test was applied. The range of age between year was 1,234 days for the cows born in 1965 and 1,574 days for those borns in 1969 (P< .01) when Tukey's test was applied. The age at first calving increased (P< .01) in the period, b = 18 days/year. The herdability coefficient was 0.38 ± 0.11.